Analyze Effectiveness of the Agritourism Development Program of Star Fruit Picking with Structural Equation Modelling (SEM) - Puspitasari, Mega Leny; Hartati, Agustina Shinta; Nugroho, Tri Wahyu (Agro Bali : Agricultural Journal, 2024)
Ngringinrejo star fruit agritourism is one of the Bojonegoro Regency regional tourism development programs, which is expected to develop from year to year to have a significant economic impact on increasing village independence. However, in the last three years, agritourism income has decreased drastically, thus affecting the economic stability of the community. This study aims to analyze the effect of program quality on the effectiveness of development programs through the mediation of information and promotion systems applied in agritourism. This study was conducted from October to November 2023 and used a quantitative method with a questionnaire to obtain information from respondents. It was chosen by probability sampling based on the Statistical Power of 80%, so the minimum number of respondents was 76 star fruit farmers in Ngringinrejo Agritourism, Ngringinrejo Village, Bojonegoro Regency, East Java. The data were analyzed using SEM-PLS, and the result shows a positive and significant influence between program quality and development program effectiveness. Meanwhile, the information and promotion system has no effect and is not significant to the effectiveness of the program, so it is not able to mediate the relationship between program quality and the effectiveness of the program. The effectiveness of the Ngringinrejo agritourism development program in terms of its impact on social, economic, and environmental aspects is considered adequate because it provides benefits for the social development of the community, a decrease in poverty levels with an improvement in the community's economy, and is proven to be able to overcome environmental problems such as soil erosion and flooding.